2018
DOI: 10.1002/eji.201847480
|View full text |Cite
|
Sign up to set email alerts
|

NCR+ ILC3 maintain larger STAT4 reservoir via T‐BET to regulate type 1 features upon IL‐23 stimulation in mice

Abstract: Innate lymphoid cells (ILCs) producing IL-22 and/or IL-17, designated as ILC3, comprise a heterogeneous subset of cells involved in regulation of gut barrier homeostasis and inflammation. Exogenous environmental cues in conjunction with regulated expression of endogenous factors are key determinants of plasticity of ILC3 toward the type 1 fate. Herein, by using mouse models and transcriptomic approaches, we defined at the molecular level, initial events driving ILC3 expressing natural cytotoxicity receptors (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 38 publications
2
32
2
Order By: Relevance
“…Thanks to the coexpression of RORγt and T‐BET, NCR + ILC3 are able to activate both genes typical of the type 3 response and genes associated with the NK cell response, even if the production of IFN‐γ requires a longer kinetics than IL‐22. We also found that selective expression of STAT4 in NCR + ILC3 is involved in amplification of IFN‐γ production in a IL‐23‐dependent manner . Thus, the combinatorial expression of LDTFs and SDTFs can modulate the outcome of cytokine signaling in ILCs.…”
Section: Jak/stat Pathway In Ilc Biologymentioning
confidence: 65%
“…Thanks to the coexpression of RORγt and T‐BET, NCR + ILC3 are able to activate both genes typical of the type 3 response and genes associated with the NK cell response, even if the production of IFN‐γ requires a longer kinetics than IL‐22. We also found that selective expression of STAT4 in NCR + ILC3 is involved in amplification of IFN‐γ production in a IL‐23‐dependent manner . Thus, the combinatorial expression of LDTFs and SDTFs can modulate the outcome of cytokine signaling in ILCs.…”
Section: Jak/stat Pathway In Ilc Biologymentioning
confidence: 65%
“…Plasticity between ILC3 and ILC1 mediated by IL-23 and also IL-12 produced by CD14 + DC promotes polarization from ILC3s toward ILC1s, which ultimately affects tumor immunosurveillance in response to various environmental changes (2,103,150). IL-23-induced activation of STAT4 in NCR + ILC3s is a key determinant of plasticity from NCR + ILC3s toward ILC1s, as demonstrated by a transcriptomic analysis (157). Moreover, ILC3-to-ILC1 transition was tissue dependent and relied on transcription factor Aiolos and T-bet cooperation to repress regulatory elements active in ILC3s.…”
Section: Ilc3s To Nk Cells Ilc1s and Ilc2smentioning
confidence: 85%
“…Finally, LTi are critical for lymphoid organogenesis (49). Beyond this, significant plasticity occurs between ILC subsets depending on environmental stimuli they receive, thus directly impacting on their effector functions and immune responses (50)(51)(52)(53)(54)(55). While ILCs are essential to lymphoid organogenesis and tissue homeostasis, they also participate to the development of autoimmune diseases (56,57) or inflammationdriven carcinogenesis (58) (Figure 1).…”
Section: The Tumor Immune Contexture In Colorectal Cancer-the Successmentioning
confidence: 99%
“…This inflammation can be exacerbated by the loss of barrier protection occurring early during CRC development (93), allowing for the infiltration of microbes and their associated products into the tumor microenvironment. This activates dendritic cells and macrophages to produce IL-23 (94), a key cytokine regulating ILC3 function and plasticity (53,95). Additional stimuli such as IL-12, IL-18, TGF-β, or Notch ligand can profoundly influence ILC3 plasticity (50)(51)(52).…”
Section: Type 3 Innate Lymphoid Cellsmentioning
confidence: 99%
See 1 more Smart Citation